Corporate Compliance as an Alternative to The Criminal Justice System in Resolving Business Crimes - Omer Faruk Tekdogan (Generate Digital Publishing, 2026)
Objective: This study critically examines whether corporate compliance has evolved from a preventive governance instrument into a de facto substitute for criminal justice in the enforcement of business and economic crimes, particularly through non-judicial settlement mechanisms. Research Design & Methods: Using a doctrinal-comparative qualitative design within a socio-legal framework, this study analyzes international journal literature on corporate compliance, Deferred Prosecution Agreements (DPAs), Non-Prosecution Agreements (NPAs), administrative settlements, and individual accountability regimes in various jurisdictions. Findings: Findings show that corporate compliance increasingly operates as a negotiation-based law enforcement tool that partially replaces formal criminal proceedings. Compliance mechanisms systematically shift law enforcement from public courts to administrative settlements and negotiations, weakening deterrence, judicial transparency, and individual accountability, especially for senior corporate actors. This transformation contributes to selective law enforcement and the emergence of a shadow justice system that favors economically powerful corporations. Implications: Replacing criminal proceedings with negotiated compliance undermines the principle of equality before the law and reduces business crime to operational risk. This study recommends a hybrid enforcement model. In this model, compliance serves as a complement to, rather than a substitute for, criminal prosecution. Contribution & Value Added: This study develops the Compliance Justice Substitution Theory, linking compliance governance with criminal justice outcomes, and provides policy recommendations to prevent the use of compliance as a tool for corporate impunity.